2003
DOI: 10.1021/bi034043e
|View full text |Cite
|
Sign up to set email alerts
|

A Novel α-Conotoxin Identified by Gene Sequencing Is Active in Suppressing the Vascular Response to Selective Stimulation of Sensory Nerves in Vivo

Abstract: We describe the identification of a conopeptide sequence in venom duct mRNA from Conus victoriae that suppresses a vascular response to pain in the rat. PCR-RACE was used to screen venom duct cDNAs for those transcripts that encode specific antagonists of vertebrate neuronal nicotinic acetylcholine receptors (nAChRs). One of these peptides, Vc1.1, was active as an antagonist of neuronal nAChRs in receptor binding and functional studies in bovine chromaffin cells. It also suppressed the vascular responses to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
157
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(167 citation statements)
references
References 24 publications
(45 reference statements)
7
157
0
3
Order By: Relevance
“…Although it is generally nAChR agonists that are reported to be analgesic, ␣-conotoxin Vc1.1, also known as ACV1, a compound in human clinical trials by Metabolic (Melbourne, Australia), is a nAChR antagonist that previously has been shown to be analgesic. Peripheral application of this peptide blocks the vascular inflammatory response to electrical stimulation of C fibers and is analgesic in CCI and partial nerve ligation models of human neuropathic pain (14,15). The previously reported subtype specificity of this analgesic peptide is for ␣3(␣5)␤2 and ␣3(␣5)␤4 nAChRs with micromolar IC 50 values (16).…”
Section: Vc1mentioning
confidence: 90%
“…Although it is generally nAChR agonists that are reported to be analgesic, ␣-conotoxin Vc1.1, also known as ACV1, a compound in human clinical trials by Metabolic (Melbourne, Australia), is a nAChR antagonist that previously has been shown to be analgesic. Peripheral application of this peptide blocks the vascular inflammatory response to electrical stimulation of C fibers and is analgesic in CCI and partial nerve ligation models of human neuropathic pain (14,15). The previously reported subtype specificity of this analgesic peptide is for ␣3(␣5)␤2 and ␣3(␣5)␤4 nAChRs with micromolar IC 50 values (16).…”
Section: Vc1mentioning
confidence: 90%
“…Among these nAChRs, the a7-nAChRs are known to be overexpressed in small-cell lung carcinomas associated with smoking (74). Results from in vitro experiments suggest that malignant growth can be halted with the use of snake neurotoxins (a-neurotoxins) or snail conotoxins (a-conotoxins) (75,76) because they are competitive antagonists of a7-nAChR (77). In vivo animal studies have further shown that a7-nAChR inhibitors, such as MLA (78,79) and a-Bgtx (80), can reverse the proangiogenic effects of nicotine and inhibit cancer cell growth (16,17,19,81,82).…”
Section: Nachr Antagonists As Potential Agents For Molecular Cancer Tmentioning
confidence: 99%
“…The α-conotoxins represent one such family that specifically target nicotinic acetylcholine receptor (nAChR) subtypes. Owing to the combination of a large variety of nAChR subunit assemblies and subunit-selective α-conotoxins, many potential novel analgesics have recently been identified (Dutton and Craik 2001;Alonso et al 2003;Sandall et al 2003;Lang et al 2005;Satkunanathan et al 2005;Olivera et al 2008;McIntosh et al 2009) α-Conotoxins, including Vc1.1, RgIA, MII and AuIB, have all been reported to potently reverse signs of neuropathic pain, particularly tactile allodynia, in animal models when administered systemically (Satkunanathan et al 2005;Klimis et al 2011).…”
Section: Introductionmentioning
confidence: 99%